Pharmacokinetics, pharmacodynamics and safety of BAY 2433334, a novel activated factor XI inhibitor, in healthy volunteers: A randomized phase 1 multiple-dose study. - Kubitza, Dagmar; Heckmann, Michael; Distler, Jana; Koechel, Annemone; Schwers, Stephan; Kanefendt, Friederike (British Journal of Clinical Pharmacology, 2022)
AIM: To evaluate BAY 2433334, an oral activated factor XI (FXIa) inhibitor, in volunteers. METHODS: Phase 1 study of healthy men at a German centre. Part A: randomized, single-blind, multiple dose-escalation study of BAY 2433334 (25/50/100 mg once daily [OD]) vs. placebo. Part B: similar design to Part A; evaluated BAY 2433334 25 mg twice daily. Part C: nonrandomized, open-label study; evaluated potential interactions between BAY 2433334 (25/75 mg OD) and midazolam (7.5 mg), a CYP3A4 index substrate. Primary variables: treatment-emergent adverse events (TEAEs; Parts A and B); area under the plasma concentration-time curve (AUC) and maximum plasma concentration of midazolam and α-hydroxymidazolam (Part C). STUDY PERIOD: 18 days plus follow-up visit. RESULTS: Parts A and B: 36 participants randomized to BAY 2433334; 12 to placebo. Part C: 48 participants assigned to BAY 2433334 plus midazolam. BAY 2433334 was well tolerated in all study parts. AUC and maximum plasma concentration of BAY 2433334 in plasma appeared dose proportional over 25-100 mg OD, with low-to-moderate variability in pharmacokinetic parameters. Multiple dosing caused minor-to-moderate accumulation and a mean terminal half-life (15.8-17.8 h) supporting once-daily dosing. Dose-dependent FXIa activity inhibition and activated partial thromboplastin time prolongation were observed. BAY 2433334 appeared to have a minor effect on AUC for midazolam (ratio [90% confidence interval]: 1.1736 [1.0963-1.2564]) and α-hydroxymidazolam (0.9864 [0.9169-1.0612]) only for BAY 2433334 75 mg OD on day 10. CONCLUSION: Multiple dosing of BAY 2433334 in healthy volunteers was well tolerated, with a predictable pharmacokinetic/pharmacodynamic profile and no clinically relevant CYP3A4 induction or inhibition.
EVALuna2:561154